Life cycle management of natural infrastructure: assessment of state of practice and current tools - Kurth, Margaret H.; Piercy, Candice D.; Jackson, C. Rhett; Lemasson, Bertrand H.; Harris, Brian D. (Frontiers in Built Environment, 2024)
Design alternatives for traditional infrastructure are often compared in terms of expected -and often narrowly defined -costs and benefits to justify the selected plan. Taking a broader life cycle perspective in the benefit-cost evaluation process helps account for potentially rare, indirect, or accruing project benefits. Natural infrastructure design alternatives are generally difficult to compare to conventional alternatives due to their distinctly different costs and benefits. Natural infrastructure differs from conventional infrastructure in terms of performance and benefit development over time, lifespan, materials, intensity of intervention needs, and social and environmental benefits. This paper presents a life cycle framework that expands conventional life cycle analysis to capture other important and relevant aspects of natural and conventional infrastructure, enabling a more complete and equitable comparison of project costs and benefits. The framework consists of four dimensions: risk mitigation performance (e.g., traditional benefit of flood risk management), co-benefits, financial costs (life cycle cost analysis), and environmental costs (life cycle assessment). The framework takes current benefit cost analysis practice for both infrastructure types into account, is informed by existing life cycle evaluation methods and tools and is responsive to the unique needs and characteristics of natural infrastructure. Components of this framework have been advanced elsewhere, including in business product management, asset management, building code development, environmental certifications, ecosystem goods and services accounting, and others, but are generally not developed for natural infrastructure. Our proposed framework provides a roadmap for development of supporting resources to conduct life cycle evaluation for natural infrastructure. Systematically grasping the temporal flow of costs and benefits of natural infrastructure, in comparison to conventional flood risk management projects, will be important as societies address vast infrastructure needs in the face of climate change.